Perbedaan Status Gizi berdasarkan Riwayat Berat Badan Lahir Rendah di Kecamatan Polokarto Kabupaten Sukoharjo - Sholihah, Ina, Luluk Ria Rakhma, S.Gz., M.Gizi, Rustiningsih, SKM., M.Kes (2017)
The most leading causes of neonatal death are retarded fetal growth, nutrition deficiency in fetus, premature birth and low birth weight (LBW). LBW is one of factors affecting the sustainability of next generation. One of long-term effects of LBW will affect nutrition status. It is due to the less mature gastrointestinal organs leading to higher risk of infection. This study was an analytical observational research using cross sectional approach with 105 respondents selected using simple random sampling. The data of LBW history ware obtained through observing KIA (Maternal and Fetal Health) book while nutritional status was obtained from the result of directly body weight and height measurement. Statistical analysis was conducted using Independent Sample T-Test. The nutritional status in under-three-years children with LBW history showed that most children (66.7%) had normal nutrition status and in those without LBW history, 92.9% had normal nutritional status. The result of statistical test showed that there was a difference of nutritional status by LBW history (p = 0.003).